A genome-wide association study for blood lipid phenotypes in the Framingham Heart Study. - Kathiresan, Sekar.; Manning, Alisa K.; Demissie, Serkalem.; D'Agostino, Ralph B.; Surti, Aarti.; Guiducci, Candace.; Gianniny, Lauren.; Burtt, Nöel P.; Melander, Olle.; Orho-Melander, Marju.; Arnett, Donna K.; Peloso, Gina M.; Ordovas, Jose M.; Cupples, L Adrienne. (2016)
Background: Blood lipid levels including low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), and triglycerides (TG) are highly heritable. Genome-wide association is a promising approach to map genetic loci related to these heritable phenotypes.; Keywords: family-based association test, generalized estimating equations.; Springer Open.